Narrativas autobiográficas da constituição da saúde mental no município de Bagé/RS: memórias do passado pela luta antimanicomial - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The present scientific study of (auto)biographical research carried out in the Academic Teaching Master of the Federal University of Pampa, Bagé Campus, aims to identify and analyze the narratives of the construction of the trajectory of the pedagogical and historical context of the Collective Mental Health in Bagé, from the newspaper Correio do Sul, from Bagé, in the 80's and 90's , autobiographical narratives of the constitution of mental health in the city of Bagé, Rio Grande do Sul: memories of the past by the anti-handicomial struggle. The source of the research is in the collection of the Tarcísio Taborda Municipal Public Archive of Bagé, and recorded its first news, in September 1914, within the Republican ideas. The methodology used is (auto)biographical, exploratory, according to the documental analysis, in a historical-critical perspective, revisiting history and its contexts through the narrative of the newspaper Correio do Sul, the researcher and his records. In a descriptive way, the work is divided in multiple moments. Since, what were the autobiographical narratives of the pedagogical and historical trajectory of the formation process of mental health in the city of Bagé during the 80's and 90's? Historical research in the Brazilian press, especially historiographical research, from reading and analysis, identifies and exposes which institutional powers were in force and which were the historical narratives and consequently the educational processes. The press holds the writing of a time and place, therefore, the scientific studies in newspapers, with emphasis on the history and trajectory of a Public Policy, which is Mental Health, constituted in the field of the country's re-democratization and the Federal Citizen Constitution of 1988. The Correio do Sul, at the time, shows that the University of the Region of Campanha was a partner in the innovations of the Movement for Social Policies and Mental Health, welcoming the specialization courses in the area under study, inclusively, pioneer in Rio Grande do Sul and Brazil, in implanting in the Psychology Course, the Curricular Component, Collective Mental Health. This and other facts demonstrate the result of a historical pedagogical trajectory with direct reflections on education, health and formation processes, actions committed to ethical, epistemological, identatory and aesthetic changes to the production of subjectivity for citizenship. The research produces data from all the publications and reports on the theme, with ample disclosure on the initial phase of mental health, courses and workshops, specializations, seminars, congresses, and the very constitution of the Psychiatric Reform and Public Policies, the articulations and institutional movements, already adhering and implanting in their curricular matrices, the theories, strategic conceptions, and pedagogies of transformations. It is seen that the Collective Mental Health Movement is the result of the interdisciplinary perspective, of a desideratum of civilization with dignity, inclusion and transformation, along with the rethinking of the institutional formations.
Keywords: Saúde mental; História; Imprensa; Educação; Narrativas (auto)biográficas; Mental health; History; Press; Education; (Auto)biographical narratives; CNPQ::CIENCIAS HUMANAS